Characterization of the Fragrant Resin from Shorea roxburghii, a Lac Insect Host Tree of Tropical Deciduous Forest in South India - Swami, Saurabh; Mohanasundaram, Arumugam; Lohot, Vaibhav D. (Indian Forester, 2024)
The natural resin exudate from the bark of Shorea roxburghii G. Don possess a unique fragrance. In this study, we have characterized the S. roxburghii resin for its physicochemical properties and chemical composition. The physicochemical properties such as melting point, ash content, volatile matter and acid number of S. roxburghii resin were determined and compared with those of S. robusta resin. The chemical compounds and groups responsible for the fragrance of this resin were determined by gas chromatography mass spectrometry (GCMS). The results revealed that S. roxburghii resin has higher volatile matter (3.21%) and lower melting point (64-65 ÂºC), ash content (0.14%) and acid number (16.88) as compared to S. robusta resin. A total of 37 compounds were identified in the S. roxburghii resin sample by GCMS. These included monoterpenoids, sesquiterpenoids and triterpenoids. The sesquiterpene hydrocarbons comprising Î² Elemene, Î² Caryophylene, Î² Farensene, Selinene, Î± Panasinsen etc., was the largest group. It was followed by triterpenoids which included Lup-20(29)-en-3-one, Î² Amyrin, Î±- Amyrin, Urs-12-en-28-al and others. The oxygenated compounds such as terpinyl acetate and caryophyllene oxide were also identified in the resin. The chemical components of the resin can be further isolated and characterized for the development of various industrial applications.